Building Civic Character Through Value-Based Civic Education Learning at the Elementary Level - Indri Febrianti; Sriyanti; Hardiansyah (Yayasan Zia Salsabila, 2025)
Civic education at the elementary school level is crucial in shaping students' character and moral values, especially considering the challenges posed by the decline of social values in society. This article aims to examine the role of values-based civic education (PKn) in building students' civic character at the elementary school level. Using a literature review method, data was collected from relevant books, journals, and articles, and then analyzed qualitatively. The research findings indicate that value-based learning methods, such as case studies, role-playing, and reflective discussions, are effective in instilling democratic values, justice, social responsibility, and active participation in students. However, challenges in implementation include limitations in human resources and facilities at schools. Nevertheless, opportunities to strengthen values-based civic education through the Merdeka Curriculum policy, teacher training, and support from parents and the community are wide open. In conclusion, values-based civic education at the elementary school level can strengthen students' character as responsible citizens, with the support of appropriate resources and policies.